A Swedish traveller in the Comoro Islands: The description of Anjouan/Nzwani by Christopher Henric Braad in 1750, translated and annotated - Jeremy Franks†; Anthony S. Cheke (Afriques)
Swedish merchant C.H. Braad’s illustrated description in 1750 of the rulers, people, crops, livestock and wildlife of ‘Johanna’ (Anjouan/Nzwani) in the Comoros is translated, with extensive annotations, from part of his manuscript account of a voyage to India on the Götha Leijon.